Effect of Dietary Supplementation of Moringa oleifera Leaf Meal On Blood Profile, Haemagglutination Potential And Testicular Activities of Rabbits - Ayo-Ajasa, Olapeju Yemisi; Abiona, John; Egbeyale, Lawrence; Fafiolu, Adeboye; Bamidele, Lawal; Fatola, Olabamiji (Polish Journal of Natural Sciences, 2023)
Forty-eight unsexed weaner rabbits of mixed breeds, with initial live weight of 710–780 g were randomly allocated into four experimental dietary treatments (0%, 15%, 30% and 45% Moringa oleifera leaf meal (MOLM)) and replicated three times with four rabbits per replicate for ten weeks. Data were collected on blood profile (haematology: packed cell volume – PCV, red blood cell counts – RBC, white blood cell counts – WBC, haemoglobin – Hb, lymphocytes, mean corpuscular and haemoglobin concentration – MCHC; serum biochemical indices: total serum protein, albumin, globulin, glucose, cholesterol, alkaline phosphate – ALP and aspartate transferase – AST) and testicular activities while haemagglutination assay was also carried out. All data generated were subjected to one-way analysis of variance in a completely randomized design. White blood cell concentration, alkaline phosphatase, aspartate aminotransferase and glucose were significantly (p < 0.05) influenced by MOLM. Highest titre was obtained at 45% MOLM while spermatogenic activities were supported by Moringa supplementation at 15% and 30% inclusion level. The study concluded that supplementation of MOLM in the diets of weanar rabbits up to 45% boost the immune systems of the rabbits as shown by increased in haemagglutination titre and normal range of blood values but decreased testicular activities.